Symmetry-Breaking in Cationic Polymethine Dyes: Part 2. Shape of Electronic Absorption Bands Explained by the Thermal Fluctuations of the Solvent Reaction Field - Masunov, Artëm E; Anderson, Dane; Freidzon, Alexandra Ya; Bagaturyants, Alexander A (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2015)
The electronic absorption spectra of the symmetric cyanines exhibit dramatic dependence on the conjugated chain length: whereas short-chain homologues are characterized by the narrow and sharp absorption bands of high intensity, the long-chain homologues demonstrate very broad, structureless bands of low intensity. Spectra of the intermediate homologues combine both features. These broad bands are often explained using spontaneous symmetry-breaking and charge localization at one of the termini, and the combination of broad and sharp features was interpreted as coexistence of symmetric and asymmetric species in solution. These explanations were not supported by the first principle simulations until now. Here, we employ a combination of time-dependent density functional theory, a polarizable continuum model, and Franck–Condon (FC) approximation to predict the absorption line shapes for the series of 2-azaazulene and 1-methylpyridine-4-substituted polymethine dyes. To simulate inhomogeneous broadening by the solvent, the molecular structures are optimized in the presence of a finite electric field of various strengths. The calculated FC line shapes, averaged with the Boltzmann weights of different field strengths, reproduce the experimentally observed spectra closely. Although the polarizable continuum model accounts for the equilibrium solvent reaction field at absolute zero, the finite field accounts for the thermal fluctuations in the solvent, which break the symmetry of the solute molecule. This model of inhomogeneous broadening opens the possibility for computational studies of thermochromism. The choice of the global hybrid exchange-correlation functional SOGGA11-X, including 40% of the exact exchange, plays the critical role in the success of our model.